Wanted dead or alive! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
The demand for dead wood for fuel and to construct fences and livestock enclosures has contributed to widespread deforestation in the Sahel. To take the pressure off surviving vegetation, villagers in Burkina Faso have been encouraged and assisted...